The role of customer engagement in the involvement-loyalty link. Issue 1 (4th February 2019) - Parihar, Prateeksha; Dawra, Jagrook; Sahay, Vinita
Abstract : Purpose: The purpose of this paper is to investigate the relationship between the different dimensions of involvement and customer engagement (CE) and analyze the influence of CE on loyalty in an online retail context. The study also tests the mediation of CE between the facets of involvement and loyalty. Design/methodology/approach: The study employed a survey for data collection from online retail website users and analyzed the data with partial least squares – structural equation modeling. Findings: The results reveal that the dimensions of involvement drive engagement differently. The risk importance and risk probability do not influence CE whereas the sign, interest, and pleasure are positively associated with CE. Furthermore, CE mediates the link between sign, interest, and pleasure dimensions of involvement and loyalty. Practical implications: This study provides insights for the managers that the perception of value from a brand starts at its product category level and values like sign, interest, and pleasure can be provided to the customers by not only brand consumption but also by engaging them with the brand. Originality/value: This is among the first studies to have empirically tested the effect of dimensions of involvement on CE and explain the role of engagement as a means for the customers to achieve expected values. It also contributes to the extant CE literature by testing its mediating role between involvement dimensions and loyalty, thus augmenting the studies, which have explored the antecedents and consequences of CE.